Obstetric outcomes after uterine balloon tamponade for postpartum hemorrhage - Adhikari, HN; Pandey, A; Singh, M; Sinha, K (Devdaha Medical Journal, 2025)
Introduction: Postpartum hemorrhage (PPH) remains a leading cause of maternal mortality globally, particularly in low-resource settings. Balloon tamponade, a minimally invasive, uterus-preserving intervention, is increasingly being used to manage refractory PPH. Methods: A hospital-based observational study was conducted at Nepalgunj Medical College from November 2024 to May 2025. A total of 39 women with refractory primary PPH requiring balloon tamponade were included. Maternal demographic characteristics, obstetric variables, balloon tamponade parameters, and clinical outcomes were analyzed using SPSS version 26.0. Categorical variables were compared using the chi-square or Fisher’s exact test, and continuous variables using the independent samples t-test. A p-value <0.05 was considered statistically significant. Results: Balloon tamponade successfully controlled hemorrhage in 89.7% (35/39) of cases. The volume of normal saline used ranged from 200 to 400 ml, with a mean of 289.2 ± 44.1 ml. Although higher inflation volumes (≥300 mL) showed a greater success rate (95.2% vs 83.3%), this difference was not statistically significant (p = 0.318). Combined balloon tamponade with adjunct medical management was associated with a significantly shorter hospital stay compared to balloon tamponade alone (3.8 ± 1.2 vs 5.1 ± 2.3 days; p = 0.03), though it required a higher number of blood transfusions (p = 0.04). Balloon tamponade success was significantly higher among women with gravidity <3, (p = 0.032). Conclusion: Balloon tamponade is highly effective for refractory primary PPH, especially with ≥300 mL inflation. Combined therapy optimized outcomes in managing refractory PPH due to atonicity.